Thioether‐Bearing Hyperbranched Polyether Polyols with Methionine‐Like Side‐Chains: A Versatile Platform for Orthogonal Functionalization. Issue 1 (7th November 2016) - Seiwert, Jan; Herzberger, Jana; Leibig, Daniel; Frey, Holger
Abstract : The synthesis of thioether‐bearing hyperbranched polyether polyols based on an AB/AB2 type copolymerization (cyclic latent monomers) is introduced. The polymers are prepared by anionic ring‐opening multibranching copolymerization of glycidol and 2‐(methylthio)ethyl glycidyl ether (MTEGE), which is conveniently accessible in a single etherification step. Slow monomer addition provides control over molecular weights. Moderate dispersities ( Đ = 1.48–1.85) are obtained, given the hyperbranched structure. In situ 1 H NMR copolymerization kinetics reveal reactivity ratios of r G = 3.7 and r MTEGE = 0.27. Using slow monomer addition, copolymer composition can be systematically varied, allowing for the adjustment of the hydroxyl/thioether ratio, the degree of branching (DB = 0.36–0.48), thermal properties, and cloud point temperatures in aqueous solution in the range of 29–75 °C. Thioether oxidation to sulfoxides enables to tailor the copolymers' solubility profile. Use of these copolymers as a versatile, multifunctional platform for orthogonal modification is highlighted. The methyl sulfide groups can be selectively alkoxylated, using propylene oxide, allyl glycidyl ether, or furfuryl glycidyl ether, resulting in functional hyperbranched polyelectrolytes. Reaction of the alcohol groups with benzyl isocyanate demonstrates successful orthogonal functionalization. Abstract : Copolymerization of 2‐(methylthio)ethyl glycidyl ether with glycidol (AB + AB2 copolymerization) leads to hyperbranched polyether structures with end groups that exhibit highly orthogonal reactivity. Both the methyl thioether end groups and the hydroxyl end groups can be further reacted with high selectivity. This feature is useful, e.g., for polymer networks bearing functional crosslinking points.